Latin American Social Medicine Association: Agenda 2009 - 2011 - Nila Heredia Miranda; Mario Rovere (Social Medicine Publication Group, 2010)
From the 14th to the 19th of November 2009 we spent five intense days during the Congress developing this electoral platform with the input offered by national delegations to all candidates for the General Coordinator position. The contributions by the national delegations demonstrated their interest in the future of ALAMES. It was an intensive learning experience for us made up of conversations with delegations and participants, the challenge and effort of incorporating the various mandates given to us by the pre-Congress courses, the round table discussions, the commission, the plenary and multiple conversations in coffe breaks and the corridors. We have also attempted to incorporate those declarations which seemed to generate the most enthusiasm and those commentaries which we heard over and over again in our conversations. Finally, we congratulate all those who have made this Congress so productive, so moving, and so diverse; the presence of social movements has expanded the diversity and wealth of voices heard at the Congress. We know from previous experiences that elections are often associated with tension. Yet elections can also serve to stimulate discussion at a Congress. In our case, the election has encouraged us to create this proposal. This is a proposal which could not have been developed prior to the Congress since it is the outcome of dialogues, expectations, and discoveries made during our conversations. We offer it to the members and institutions associated with ALAMES as a roadmap for their commentary, discussion, and criticism.